The effect of technological pedagogical content knowledge (TPACK) based blended learning environment on pre-service science teachers’ TPACK and classroom practices - Kılıç, Aygün; Aydemir, Selçuk; Kazanç, Sefa (Ankara University, 2019)
The purpose of this study is to investigate the effect of the TPACK based blended learning environment on pre-service science teachers’ (PSTs’) TPACK and classroom practices involving the topics of day-night, and seasons. This study was carried out upon 37 fourth grade PSTs in Science Teacher Education Program. In this study based on one group pretest-posttest design, individual semi-structured interview based on vignette for the PSTs’ TPACK, and field notes, video records and observation protocols for the PSTs’ classroom practices were used as data collection tools. According to the findings of this study, it was found that there was a significant difference in favor of the post-test results between the pre-test and post-test about PSTs’ TPACK and classroom practices involving the topics of day-night, and seasons. The results indicated that TPACK-based blended learning environment made important contribution to the development of PSTs’ TPACK and classroom practices. © 2019, Ankara University. All rights reserved.
Teknolojik pedagojik alan bilgisi (TPAB) temelli harmanlanmış öğrenme ortamının fen bilimleri öğretmen adaylarının tpab ve sınıf içi uygulama becerilerine etkisi
Keywords: Blended learning environment; Classroom practices; Preservice teacher education; Technological Pedagogical Content Knowledge (TPACK)